2020
DOI: 10.3390/jcm9051353
|View full text |Cite
|
Sign up to set email alerts
|

Cholangiocarcinoma as an Indication for Liver Transplantation in the Era of Transplant Oncology

Abstract: Cholangiocarcinoma (CCA) arises from the biliary tract epithelium and accounts for 10–15% of all hepatobiliary malignancies. Depending on anatomic location, CCA is classified as intrahepatic (iCCA), perihilar (pCCA) and distal (dCCA). The best treatment option for pCCA is liver resection and when a radical oncological surgery is obtained, 5-year survival rate are around 20–40%. In unresectable patients, following a specific protocol, liver transplantation (LT) for pCCA showed excellent long-term disease-free s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 126 publications
(141 reference statements)
0
27
0
2
Order By: Relevance
“…PHCCA is the most common type (50%), followed by DCCA (40%) and IHCCA (10%)[ 10 ]. According to its pattern of growth and macroscopic appearance, CCA may present in three different types: Mass-forming (which presents with a mass), periductal-infiltrating (growing along the wall of the bile duct) and intraductal-growing (with intraluminal growth)[ 117 , 118 ]. The mass-forming type is by far the most frequent[ 118 ](Figure 2 ).…”
Section: Anatomical Location and Macroscopic Morphology Of Ccamentioning
confidence: 99%
“…PHCCA is the most common type (50%), followed by DCCA (40%) and IHCCA (10%)[ 10 ]. According to its pattern of growth and macroscopic appearance, CCA may present in three different types: Mass-forming (which presents with a mass), periductal-infiltrating (growing along the wall of the bile duct) and intraductal-growing (with intraluminal growth)[ 117 , 118 ]. The mass-forming type is by far the most frequent[ 118 ](Figure 2 ).…”
Section: Anatomical Location and Macroscopic Morphology Of Ccamentioning
confidence: 99%
“…Recently, the liver transplantation option has been considered in some specific disease conditions. For example, liver transplantation in unresectable pCCA preceded by neoadjuvant chemoradiotherapy showed admirable long-term disease-free survival rates [ 17 , 18 ]. Recently it has been demonstrated that very early iCCA patients after liver transplantation present good oncologic and survival outcome, although more confirmations are needed, such as the clarification of the systemic neoadjuvant regimens to be associated [ 19 , 20 ].…”
Section: Current Therapeutic Intervention In Cholangiocarcinomamentioning
confidence: 99%
“…200 The second most common hepatic liver cancer after HCC is cholangiocellular carcinoma (CCC), which arises from the malignant growth of cholangiocytes, the biliary tract epithelium, and accounts for approximately 10 to 15% of all hepatobiliary malignancies. 201,202 Current screening methods include ultrasound, computerized tomography, magnetic resonance imaging, serum biomarker assessment, and biopsy analysis 203,204 ; however, positive diagnosis can often be difficult through medical imaging and biomarker methods, 205 while a biopsy sample may misrepresent the liver due to the heterogeneity of tumor growth. 206 After diagnosis, treatments for liver cancer include transarterial chemoembolization, ablation, chemotherapy and radiation therapy, molecularly targeted therapies, surgical resection, or orthotopic liver transplantation.…”
Section: Liver Cancermentioning
confidence: 99%